Pengaruh Kompetensi Personel dan Teknologi Informasi terhadap Efektivitas Kodifikasi Materiel Bekal Di Kementerian Pertahanan - Solikhin, Dede; Marsono, Marsono; S., Waras Didik; A., Sovian; A., Andi (Akademi Angkatan Udara, 2022)
This research is motivated by the gap in the effectiveness of the material codification of supplies at the Defense Ministry's Baranahan Codification Center (Puskod Baranahan Kemhan) which is faced with the real conditions that exist. This study aims to determine the effect of personnel competence, and information technology on the effectiveness of the material codification of supplies at the Baranahan Puskod, Kemhan. The purpose of this study to analyze the effect of personnel competence and Information Technology on the effectiveness of the material codification of provisions at the Defense Facilities Agency Codification Center of the Ministry of Defense. The method used is quantitative with a descriptive statistical approach. Data collection in this study was carried out using a questionnaire/questionnaire that was given/distributed to the respondents (Puskod Baranahan Kemhan employees) as many as 54 people and processed using SPSS Statistic 25.0. Based on the research, the authors propose suggestions, namely: the Minister of Defense of the Republic of Indonesia to be used as a consideration in determining further policies related to the effectiveness of codification in the Ministry of Defense of the Republic of Indonesia. In addition, the Head of the Defense Facilities Agency of the Ministry of Defense should give important attention to increasing the competence of personnel and meeting the needs of information technology facilities in order to support the effectiveness of codification at the Baranahan Puskod of the Ministry of Defense. The last suggestion is that the Puskod Baranahan personnel of the Ministry of Defense always strive to continue to improve their competence through education and training, both at home and abroad.